2018
DOI: 10.1093/europace/euy233
|View full text |Cite
|
Sign up to set email alerts
|

A left bundle branch block activation sequence and ventricular pacing influence voltage amplitudes: anin vivoandin silicostudy

Abstract: Aims he aim of this study was to investigate the influence of the activation sequence on voltage amplitudes by evaluating regional voltage differences during a left bundle branch block (LBBB) activation sequence vs. a normal synchronous activation sequence and by evaluating pacing-induced voltage differences. Methods and results wenty-one patients and three computer models without scar were studied. Regional voltage amplitudes were evaluated in nine LBBB patients who underwent endocardial electro-anatomic mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Most previous studies focused on the LV, where we found a lowering effect of RA pacing and no effect of RV or LV pacing. Our result for RV pacing in the LV is comparable to a study by Nguyên et al on patients with left bundle branch blocks, where RV pacing did not change the overall unipolar VA in the epicardial LV [11]. Similarly to our study, the absolute values varied considerably.…”
Section: Effect Of Pacing Location On Voltage Amplitudesupporting
confidence: 89%
See 1 more Smart Citation
“…Most previous studies focused on the LV, where we found a lowering effect of RA pacing and no effect of RV or LV pacing. Our result for RV pacing in the LV is comparable to a study by Nguyên et al on patients with left bundle branch blocks, where RV pacing did not change the overall unipolar VA in the epicardial LV [11]. Similarly to our study, the absolute values varied considerably.…”
Section: Effect Of Pacing Location On Voltage Amplitudesupporting
confidence: 89%
“…Substrate mapping is employed in this context to identify areas such as local abnormal ventricular activities (LAVA) [2], zones of slow conduction [3], low voltage areas [4,5], and complex fractionated atrial electrograms (CFAE) [6]. The visibility of these crucial regions often depends on the strategy of pacing, [7][8][9][10][11][12], as conduction is typically faster along the cardiac fibers than it is across them [13,14]. To accurately interpret the changes induced by pacing, understanding the physiological variations in VC and VA during this process is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the centres of mass of LGE and AEMM surfaces were aligned using a three-dimensional translation, then an iterative closest-point approach was used to minimize the Euclidean distance between the electrodes and the endocardial contours traced on CMR images. 13 What's new?…”
Section: Integration Of Late Gadolinium Enhancement Cardiovascular Magnetic Resonance With Anatomo-electromechanical Mappingmentioning
confidence: 99%
“…Invasive (Q-LV, RV-LV interval, and ECG imaging) seems more useful, especially when combined with scar imaging in order to avoid positioning of the lead in a scarred region. 13 The growing availability and adoption of ECG-imaging technologies may facilitate the accurate identification of the site of latest electrical activation. However, the benefit of these non-invasive electrical approaches needs to be supported by future trials.…”
Section: Clinical Implications For Cardiac Imaging Selectionmentioning
confidence: 99%
“…Modeling Challenge References healthy heart-QRS modeling the Purkinje tree [1][2][3][4][5][6][7][8][9] healthy heart-T-wave modeling heterogeneity of repolarization [10][11][12][13] healthy heart-P-wave modeling sinus node excitation and pathways from right to left atrium, anatomical variability [14][15][16][17][18][19][20][21][22] ischemia and infarction modeling the effect of hyperkalemia, acidosis, hypoxia and cell-to-cell uncoupling [23][24][25][26][27][28][29][30] ventricular ectopic beats localization with 12-lead ECG [31][32][33][34] ventricular tachycardia localization of exit points with 12-lead ECG [29,35] cardiomyopathy modeling typical changes of QRS-and T-wave [36] bundle branch blocks LBBB and RBBB modeling asynchrony [37][38][39][40] atrial ectopic beats localization with 12-lead ECG [32][33][34] atrial tachycardia, flutter modeling all types of flutter…”
Section: Topicmentioning
confidence: 99%